2021
DOI: 10.1073/pnas.1922305118
|View full text |Cite
|
Sign up to set email alerts
|

A model and test for coordinated polygenic epistasis in complex traits

Abstract: Interactions between genetic variants—epistasis—is pervasive in model systems and can profoundly impact evolutionary adaption, population disease dynamics, genetic mapping, and precision medicine efforts. In this work, we develop a model for structured polygenic epistasis, called coordinated epistasis (CE), and prove that several recent theories of genetic architecture fall under the formal umbrella of CE. Unlike standard epistasis models that assume epistasis and main effects are independent, CE captures syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 109 publications
1
28
0
Order By: Relevance
“…Conversely, if the SNP main effects have no correlation with the SNP interaction effects with the drug (''uncoordinated interactions''), then there is no power to detect a significant interaction. 37,38 Based on this, we can conclude that testing for a polygenic-drug interaction is an effective approach for assessing the relationship between main and interaction effects and thereby identifying drugs that modulate genetic risk. Furthermore and importantly, PGSs incorporate variation from multiple pathways.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Conversely, if the SNP main effects have no correlation with the SNP interaction effects with the drug (''uncoordinated interactions''), then there is no power to detect a significant interaction. 37,38 Based on this, we can conclude that testing for a polygenic-drug interaction is an effective approach for assessing the relationship between main and interaction effects and thereby identifying drugs that modulate genetic risk. Furthermore and importantly, PGSs incorporate variation from multiple pathways.…”
Section: Resultsmentioning
confidence: 93%
“…Introduction to coordinated interactions through the lens of drug response As described previously by Sheppard et al 37 and Aschard, 38 statistical interactions between PGSs and other factors are driven by SNPs broadly interacting positively or negatively in a model named a coordinated interaction. Thus, a significant interaction between PGS and drug use (a ''polygenicdrug interaction'') with regard to a particular phenotype means that drug use serves to strengthen or dampen-on average-the marginal genetic effects of causal variants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in part due to the longstanding and ongoing debate about the contribution of non-additive effects (e.g., epistasis and dominance effects) on the architecture of human complex traits [16][17][18][19][20][21][22][23][24][25][26] . However, despite these controversies, many association mapping studies in humans have identified candidates of epistasis that notably contribute to trait variation [27][28][29][30][31] , and some have recently shown that gene-by-gene interactions can drive heterogeneity of causal variant effect sizes across diverse human populations 32 . Epistasis is a well-known contributor to trait architecture in several model organisms [33][34][35][36][37][38][39][40][41][42][43][44] .…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted August 15, 2022. ; https://doi.org/10.1101/2022.08.13.503863 doi: bioRxiv preprint 3 on datasets oriented in a sample-wise fashion. Lastly, there is significant evidence that there is a small, but significant non-additive component to the heritability of complex human traits [10], [11]. Modeling these nonlinearities is facilitated by data structures organized by sample.…”
Section: Introductionmentioning
confidence: 99%